(untitled) (LEARNing Landscapes, 2007)
This paper draws on my Ph.D thesis, An ordinary teacher: An autoethnography, which is a teacher self-study where I revisit my experiences in the field of education. Through the use of stories I explore personal experiences to come to a deeper understanding of myself, and my practice, allowing others to reflect on theirs. The article discusses the meaning of lived experience and and the terms and synergies pertaining to student and teacher engagement.